(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Thyroid gland pathology is considered a marker of environmental distress. The most significant morphophysiological structure of the thyroid gland is a tissue microregion that combines a group of follicles and interfollicular space with an autonomous system of blood and lymph circulation. It is the structures of the tissue microregion that suffer the most under the action of pathogenic factors on the thyroid gland, diminishing its role in facilitating morphological and metabolic changes in tissues and organs [Borodin Yu.I., et al., 2018]. However, the morphological and morphometric changes in the thyroid gland during polypharmacy with anti-inflammatory drugs are poorly understood. This article presents a review of the literature on structural changes in the thyroid gland during polypharmacy with anti-inflammatory drugs.